Paradoxes of French accreditation. Issue 1 (3rd February 2005) - Pomey, M-P; François, P; Contandriopoulos, A-P; Tosh, A; Bertrand, D
Abstract : The accreditation system introduced into the French healthcare system in 1996 has five particular characteristics: (1) it is mandatory for all healthcare establishments; (2) it is performed by an independent government agency; (3) surveyors have to report all instances of non-compliance with safety regulations; (4) the accreditation report is delivered to regional administrative authorities and a summary is made available to the public; and (5) regional administrative authorities can use the information contained in the accreditation report to revise hospital budgets. These give rise to a number of paradoxes: (1) the fact that accreditation is mandatory lends itself to ambiguity and likens the process to an inspection; (2) the fact that decision makers can use the information contained in the accreditation report for resource allocation can incite establishments to adopt strategic behaviours aimed merely at complying with the accreditation manual; and (3) there is a tendency for establishments to reduce quality processes to nothing more than the completion of accreditation and to focus efforts on standardizing practices and resolving safety issues to the detriment of organizational development. All accreditation systems must be aware of these paradoxes and decide on the level of government involvement and the relationship between accreditation and resource allocation. With time, accreditation in France could benefit from both a professionally driven system and from the increased amount of freedom to focus on quality improvement which is necessary for organizational development.